Energy-Efficient Modes of Dehydration of Pome Fruits during Microwave Treatment in Combination with Convection - Popescu V.; Vishanu V.; Balan M.; Melenchiuc M.; Volconovich O.; Balan T. (Problems of the Regional Energetics)
The aim of the work is to significantly increase the efficiency of the dehydrating process of fruits with seeds, by treating it with microwaves in combination with convection. To achieve the purpose, an electrical installation was designed, produced, tested, optimized and implemented, which applies the combined technological treatment method in the dehydration process. Pears were selected as the object of the research in particular, because currently the production of these seeded fruits is not fully exploited, but they are of an increased interest for the agricultural producers and for specialized enterprises, and their dehydration by the methods currently used is difficult, especially because of the browning effect that occurs in the heat treatment process. The essential results obtained based on the research carried out, regarding the application of the elaborated installation, are: reduction of electricity consumption and treatment duration, increase in productivity and quality of dehydrated fruits. At the same time, the developed installation is simple in construction, has low cost and is easy to use, and during fruit processing it allows strict monitoring of the technological parameters, and researches demonstrated a high level of safety in operation. The significance of the obtained results lies in the solution to a series of problems, which are currently faced by the enterprises specialized in fruit processing, in particular by significantly increasing the efficiency of the process of dehydration of pears, based on the proposed method of combined treatment, predominantly with increasing the speed of dehydration, energy efficiency, quality of final products and profitability.